Traumatic splenic hematoma 13 days of evolution - Schneeberger, Federico; Piñeyro, Alberto; Farcic, Antonio (Cirugía del Uruguay, 1978)
This paper describes the case of a patient with traumatic splenic hematoma operated 18 days after trauma. Conventional X - ray and pneumoperitoneum are important in preoperatory diagnosis.